ANALYSIS OF THE STRUCTURE AND WORKING PARTS OF SAW GINNING MACHINES (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This paper reviews the structure and function of saw ginning machines and fiber cleaners, focusing on models like 4DP-130 and 8DP-90. It presents technical improvements that enhance fiber quality and ginning efficiency.